Nickel–Aluminum Intermetallic Compounds as Highly Selective and Stable Catalysts for the Hydrogenation of Naphthalene to Tetralin. Issue 6 (6th February 2015) - Chen, Xiao; Ma, Yue; Wang, Lei; Yang, Zonghan; Jin, Shaohua; Zhang, Liangliang; Liang, Changhai
Abstract Selective hydrogenation of naphthalene to tetralin was conducted by using Ni–Al intermetallic compounds (IMCs) prepared by a chemical synthetic route. Ni–Al IMC catalysts achieved a lasting high conversion with 100 % selectivity up to 125 h. During the synthesis process, the Ni–Al IMCs underwent the following phase transformation as a function of the content of the Al source (LiAlH4): Ni(cubic)→Ni3Al(tetragonal)→NiAl(cubic)→Ni2Al3(hexagonal). In the selective hydrogenation of naphthalene, the catalytic activity of NiAl was much higher than that of metallic Ni and other Ni–Al IMCs (Ni3Al and Ni2Al3). The results can be understood by a combination of site isolation and alteration of the electronic structure by chemical bonding. Ni atoms are scattered and spatially isolated by Al atoms, which in turn resists carbon deposition. The findings provide a useful approach to tailor the catalytic properties of transition metals by formation of IMCs, which could be applicable in heterogeneous catalysis.